Oral food challenge in children affected by egg allergy: why complicate pediatric allergist’s life? - Pecoraro, Luca; Chiaffoni, Giovanni; Widhalm, Kurt; Arnone, Olivia Chapin; Piacentini, Giorgio; Pietrobelli, Angelo (Acta Biomedica Atenei Parmensis, 2024)
The assessment of the tolerance in children affected by egg allergy is to perform an oral food challenge (OFC) using fresh raw egg (FRE). This technique has infectious risk and administration issues. This study aims to evaluate the efficacy of a simplistic method to perform OFC using pasteurized raw egg white (PREW). It is a retrospective study involving 9 children affected by egg allergy that attended our pediatric allergy unit and underwent to an OFC using PREW to assess their potential egg tolerance. 100% of children had a positive skin prick test. sIgE related to white egg was positive in 87.5% of children. 77.7 % of patients had a negative OFC result. 22.3 % of children had a positive OFC. All children with a negative OFC had no allergic issues after two months. The use of PREW white instead of FRE in OFC could be an effective method in the assessment of the tolerance in children affected by egg allergy. It could have significant advantages in terms of infectious risk and way of administration.